2002
DOI: 10.1262/jrd.48.303
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Activities of Hydroxysteroid Dehydrogenases in Porcine Oocytes during Meiotic Maturation In Vitro.

Abstract: Abstract. The activities of hydroxysteroid dehydrogenases (HSDs) were histochemically demonstrated in cultured porcine oocytes, and the changes in steroid metabolism during meiotic maturation and also the relationship between nuclear maturation and changes in steroid metabolism in the cytoplasm were examined. The activities of ∆ 5 -3β-HSD, 17β-HSD, 20α-HSD and 20β-HSD were observed in 91 to 97% of porcine oocytes soon after collection. The percentages of oocytes showing the activities of ∆ 5 -3β-HSD (using DHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…From the results of the present investigation and that of Ta kano and Niimura [3 ], it was confirmed that changes in the metabolic abilities of steroids in oocytes with maturation are different in pigs and mice, and that there are animals with and without a relationship between nuclear maturation and changes in steroid metabolism in the oocytes.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…From the results of the present investigation and that of Ta kano and Niimura [3 ], it was confirmed that changes in the metabolic abilities of steroids in oocytes with maturation are different in pigs and mice, and that there are animals with and without a relationship between nuclear maturation and changes in steroid metabolism in the oocytes.…”
Section: Discussionsupporting
confidence: 82%
“…As already mentioned, the metabolic abilities of progesterone, 17α-hydroxyprogesterone, 17α,20β-dihydroxyprogesterone, 20α-hydroxyprogesterone and estrogen weakened and disappeared in porcine oocytes with the progression of nuclear maturation [3]. From the results of the present investigation and that of Ta kano and Niimura [3 ], it was confirmed that changes in the metabolic abilities of steroids in oocytes with maturation are different in pigs and mice, and that there are animals with and without a relationship between nuclear maturation and changes in steroid metabolism in the oocytes.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Here, we demonstrate that the level of 20a-HSD mRNA expression, which was high in immature COCs, dramatically decreased throughout the IVM and IVF periods to reach its lowest levels in fertilized COCs. A previous in vitro study of porcine COCs had reported that 20a-HSD activity was closely related to oocyte nuclear status (Takano & Niimura 2002). The 20a-HSD activity present in immature COCs decreased during IVM to disappear at the metaphase II stage.…”
Section: Discussionmentioning
confidence: 80%